Tindakan Preventif Dampak Pinjaman Online Sebagai Potensi Kegiatan Pengabdian Masyarakat - Alfiana; Pri Handini, Dharmayanti (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
Online loans (pinjol) are a growing money lending service. This application has a negative impact on the user community. Various research and community service activities have been carried out. This article aims to describe preventive treatments for the impact of online loans as potential community service activities. The description is carried out with a brief review based on the publication of community service activities that have been carried out. The results of the review show that legal and economic aspects are the main topics of activity. Activities are carried out using the socialization method with the target group of the public community and among housewives. The potential targets for the next community service activities in this area are teachers and layoff victims as the two top list of loan victims. The scope of new activities can be directed at the security of digital transactions and the impact of knowledge in minimizing negative effects.